Analisis Alur Proses Permintaan Bahan Baku Plat Besi dan Alur Proses Penerimaan Material Bahan Baku Plat Besi PT. Nichias Rockwool Indonesia - Abudzar Alghifari; Wahyudin Wahyudin; Kusnadi Kusnadi (Jurnal Ilmiah Wahana Pendidikan, 2021)
PT. Nichias Rockwool Indonesia or can be called PT. NRI located in Kujang Cikampek Area of West Java is engaged in thermal insulation that produces and also engages in repair services with a wide industrial reach for more than 100 years. PT Nichias Rockwool Indonesia consists of several interrelated departments and synergizes to realize the company's goals. Inventory is one of the important elements in the operation of a company. In the absence of inventory the company will be faced with the risk of not being able to meet the needs of consumers so that it will lose the opportunity to get profits that result in targets to consumers not being met, decisions regarding how much and when to place orders are considered in inventory issues, especially if the need consists of several types of products from different suppliers with a limited budget. One of the raw materials needed in the process of making thermal insulation is iron plate, the raw material is obtained from other companies engaged in iron manufacturing and has cooperated with PT. Nichias Rockwool Indonesia. To maintain the imbalance, the company needs to do planning between production and material needs in order to meet the production stock in PT. Nichias Rockwool Indonesia and meets the needs of consumers.